DOI: 10.20378/irb-54906
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Abusive Supervision via Leader Narcissism : The Role of Narcissistic Leaders' Internal Processes and Follower Behaviors

Abstract: With the current dissertation, I aimed to shed light on antecedents of abusive supervision from a leader perspective. First, I investigated whether leader narcissism is associated with abusive supervision (Research Question 1). Building on a two-dimensional approach to narcissism (Back et al., 2013), I differentiated between leaders’ narcissistic rivalry and admiration. Second, building on threatened egotism theory (Baumeister, Smart, & Boden, 1996; Bushman & Baumeister, 1998), I examined which underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Studies confirmed that narcissistic leaders possess self-centeredness and demand for higher admiration that may not leave a positive impact on employees (Carnevale et al, 2018;Gauglitz, 2022). While knowledge sharing in a team is not an automatic process, the team's leader has great capability to strongly influence knowledge sharing (Khalid et al, 2018) Furthermore, literature shows the impact of destructive or dark leadership on various components like turnover intentions, job satisfaction, lifestyle dissatisfaction, and job performance (Tepper, 2000).…”
Section: Narcissistic Leadership and Knowledge Sharingmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies confirmed that narcissistic leaders possess self-centeredness and demand for higher admiration that may not leave a positive impact on employees (Carnevale et al, 2018;Gauglitz, 2022). While knowledge sharing in a team is not an automatic process, the team's leader has great capability to strongly influence knowledge sharing (Khalid et al, 2018) Furthermore, literature shows the impact of destructive or dark leadership on various components like turnover intentions, job satisfaction, lifestyle dissatisfaction, and job performance (Tepper, 2000).…”
Section: Narcissistic Leadership and Knowledge Sharingmentioning
confidence: 98%
“…Narcissistic personality traits are more likely to have negative implications for organizations as compared to positive implications as it is associated with psychological distress, anxiety, negative emotions, entitlement, interpersonal dominance, and a distrustful approach to interpersonal relations (Kaufman et al, 2020). Narcissistic leadership is perceived as a negative leadership trait that may be attributed to negative interpersonal behavior inside the working environment (Gauglitz, 2022;Neumann et al, 2021;Wang et al, 2021). Therefore, this study intends to advance the extant knowledge regarding how narcissistic leadership affects project success.…”
Section: Introductionmentioning
confidence: 99%